German-Polish relations. Political and economic aspects - Ulatowski, Rafał (UNISCI Journal, 2016)
The aim of this article is to analyze the Polish-German relations in the last 25 years. The article will concentrate on the expectations declared in the early 1990s as well as on the results that were achieved. I argue that economic strength was successfully used by the German government to give German-Polish relations a new quality. Polish-German relations are an example of successful implementation of geo-economics strategy by the German government.